Defining burnout syndrome in a population of nurse educators - Tasić, Radica; Stojanovic, Dragica; Jovicic, Ljiljana (Education and Research in Health Sciences, 2026)
Introduction: Bad interpersonal relations, mobbing, anxiety contribute to the development of burnout syndrome at work, and all together lead to psychological and physiological changes in employees, resulting in the development of depression and organic diseases. Method: This cross-sectional study included 302 nurse educators employed in preschool institutions on the territory of Belgrade. The goal: Assessment of the prevalence of burnout syndrome at work, analysis of psychometric characteristics of the measuring instrument, definition of predictors of burnout syndrome at work and definition of a model of connection between psychological personality characteristics and burnout syndrome. Results: The average age in the studied population was 38+9.2 (range 16-60 years) and all were female. The average length of work experience was 11 years (percentile 6-18) and the majority had completed high school (79.7%). The average score of the exhaustion subscale was 1.5+1.3. A moderate to high level of exhaustion was observed in 27.6% of nurse educators. The average score of the subscale for professional efficiency was 5.3+0.7, and the scores for low, moderate and high burnout were represented in 78.8%, 16.1% and 5.1%. The average score of the subscale for cynicism was 1.6+1.1. In total, 251 (83.1%) nurse educators had moderate burnout syndrome. aggressiveness, neuroticism and negative valence were positively correlated with exhaustion (p < 0,001). Conclusion: The job of a nurse-educator requires a high level of social responsibility, and everyday problems that can arise include work overload, lack of autonomy or decision-making authority, and difficulty balancing family life and work. Work overload due to lack of staff is often present. All of these factors make nurse educators particularly vulnerable to burnout.